2016
DOI: 10.1021/acschemneuro.6b00069
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Ganglioside Hp-s1 Analogues Varying at Glucosyl Moiety

Abstract: Ganglioside Hp-s1 is isolated from the ovary of sea urchin Diadema setosum. It exhibited better neuritogenic activity than GM1 in pheochromocytoma 12 cells. To explore the roles of glucosyl moiety of Hp-s1 in contributing to the neurogenic activity, we developed feasible procedures for synthesis of Hp-s1 analogues (2a-2f). The glucosyl moiety of Hp-s1 was replaced with α-glucose, α-galactose, β-galactose, α-mannose, and β-mannose, and their biological activities on SH-SY5Y cells and natural killer T (NKT) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Hp-s1 and Hp-s1A have only two saccharide bases. Replacing the glycosyl moiety reduces the neuritogenic activities of Hp-s1 . The saccharide portion of a ganglioside may play an important role in the interaction with hydrophilic regions of a protein or other molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hp-s1 and Hp-s1A have only two saccharide bases. Replacing the glycosyl moiety reduces the neuritogenic activities of Hp-s1 . The saccharide portion of a ganglioside may play an important role in the interaction with hydrophilic regions of a protein or other molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Replacing the glycosyl moiety reduces the neuritogenic activities of Hp-s1. 28 The saccharide portion of a ganglioside may play an important role in the interaction with hydrophilic regions of a protein or other molecules. In addition to the saccharide composition, the ceramide structures in these gangliosides are also different.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%
“…The same authors carried out an SAR study involving the synthesis of six Hp-s1 analogues ( 156 – 161 ) by replacing the glucosyl unit of Hp-s1 with α-glucose ( 157 ), α- and β-galactose ( 158 and 159 ), and α- and β-mannose ( 160 and 161 ), including the simple cerebroside 156 [ 66 ]. After the biological evaluation, the authors found that the C-2 hydroxyl group of the glucosyl unit played a crucial role in the stimulation of neurite outgrowth of SH-SY5Y cells.…”
Section: Chemistry and Biology Of Glycosphingolipidsmentioning
confidence: 99%
“…[11] Recently,w ep ublished the ganglioside Hp-s1 and its derivatives for the study of neurological efficacy. [12] Am onomethylated ganglioside, DSG-A,w as isolated from the ovary of the sea urchin Diademas etosum and reported by Highuchie tal. [13] Tsai and co-workers published the first synthesis of ganglioside DSG-A.…”
mentioning
confidence: 92%